Manuais de redação de Leonor Posada: as concepções de língua e as propostas de ensino para a produção textual - Felga, Tatiana Emanuele Brito (2009)
This study aims to examine two manuals essay written by Leonor Posada in the 1940s, to highlight the concept of language and its relationship with the educational politics force. His books coincide with the introduction of Commission National Textbook, an initiative of State in the management of the Minister of Education Gustavo Capanema. Works clearly obey the restrictions of Reform, both in relation to the use of cultivated language, and in relation to education advocated by the School New. This work thus aims to contribute to History of Linguistic Ideas